Do Self-Expanding Metal Stents as a Bridge to Surgery Benefit All Patients with Obstructive Left-Side Colorectal Cancers? - Jun-rong Zhang; Ping Hou; Tian-ran Liao; Yong Wei; Xian-qiang Chen; Bing-qiang Lin (Gastroenterology Research and Practice)
Background. Self-expanding metal stents (SEMS) have been increasingly used in patients with obstructive left-sided colorectal cancer (OLCC); however, stent-specific complications (e.g., perforations) might worsen the long-term survival outcome. Strict indication needed to be identified to confirm the benefit subgroups. This study was designed to explore the indication for emergency surgery (ES) and SEMS in patients with OLCC and to suggest optimal strategies for individuals. Methods. After propensity score matching, 36 pairs were included. Perioperative and long-term survival outcomes (3-year overall survival (OS) and 3-year disease-free survival (DFS)) were compared between the ES and SEMS groups. Independent risk factors were evaluated among subgroups. Stratification survival analysis was performed to identify subgroups that would benefit from SEMS placement or ES. Results. The perioperative outcomes were similar between the SEMS and ES groups. The 3-year OS was comparable between the SEMS (73.5%) and ES (60.0%) groups, and the 3-year DFS in the SEMS group (69.7%) was similar to that in the ES group (57.1%). The pT stage was an independent risk factor for 3-year DFS (p=0.014) and 3-year OS (p=0.010) in the SEMS group. The comorbidity status (p=0.049) independently affected 3-year DFS in the ES group. The 3-year OS rate was influenced by the cM stage (p=0.003). Patients with non-pT4 stages in the SEMS group showed obviously better 3-year OS (95.0%) than the other subgroups. The 3-year OS rate was 36.4% in the ES group when patients had a worse comorbidity status than their counterparts. Conclusion. SEMS might be preferred for patients of obstructive left-sided colorectal cancer in the “high-operative risk group” with existing comorbidities or those without locally advanced invasion, such as the non-pT4-stage status.